Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Water quality assessment in multi-salinity groundwater of muddy coastal zones using a function-adaptive weight water quality index - Qiming Sun; Xinyue Chang; Rui Xu; Xin Ji; Jianhe Yang; Hongwei Liu; Maosheng Gao; Guohua Hou; Zhenlin Liu; Xianmin Ke; Jie Dong (Journal of Contaminant Hydrology, 2026)

Advanced electric field technologies for postharvest preservation of fresh fruit and vegetables: Applications, mechanisms and future perspectives - Ben Yu; Dongyang Xu; Tingshi He; Jiangshan Qiao; Junhu Cheng; Xin-An Zeng; Rui Wang (Postharvest Biology and Technology, 2026)

Integrating optical remote sensing and airborne gamma for lithological classification using an artificial neural network: A case study in Wuliji, North China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

From charge dependence to host-guest recognition: A reliable CZE method for simultaneous separation and determination of flavonoid glycosides with similar structures - Rui Zhang; Biying Guo; Xin Zhou; Fuyu Yang; Yong Xu (Food Chemistry, 2026)

Evolution of lipid profiles, microbiota succession, and potential warmed-over flavor markers in prepared squid (Dosidicus gigas) during extended refrigerated storage: A multi-omics study - Xin Zhang; Rui Tan; Chengxin Lv; Zhiyuan Xiao; Kang Guo; Bin Zhang; Ru Song; Yan Xu; Wei Xia (Food Bioscience, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

Metagenomic insights into Thermus-mediated sulfur oxidation, nitrogen cycling, and thermoadaptation in thermophilic autotrophic denitrification bioreactors - Yuan-Yuan Xu; Xin Tan; Cheng-Cheng Dang; Zhi-Cheng Zhao; Rui Fang; Liang Fan; Nan-Qi Ren; Guo-Jun Xie; Yi-Ning Wu (Bioresource Technology, 2026)

Paleoenvironmental response in the South China Sea from the Middle Miocene Climatic Optimum to Middle Miocene Climate Transition: Geochemical records from an isolated carbonate platform - Ning Guo; Wei Jiang; Tianlai Fan; Shendong Xu; Rui Wang; Jian-xin Zhao; Yue-xing Feng; Kefu Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Engineered probiotic carriers enregulate coordinated cuproptosis and ferroptosis with immune activation against bladder cancer - Anguo Zhao; Rongkang Li; Rui Liang; Qi Zhuang; Yang Liu; Dashi Deng; Peng Yu; Lei Peng; Hongbo Xu; Jun Zhang; Zhangxin He; Xin Chen; et al. (Chemical Engineering Journal, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

CWN-Net: a precise segmentation model for composite water networks using multi-source and multi-temporal remote sensing imagery - Mingyang Li; Huimin Lei; Fulin Li; Jiwen Huang; Yuzhi Shi; Shangjie Xu; Han Wang; Sinan Wang; Rui Wang; Lili Liu; Suzhen Cheng; Lei Guo; et al. (Journal of Hydrology, 2026)

Pulsed electric field processing of buffalo milk with retained Joule heating: Microbial efficacy, bioactive protein retention, and flavor profiling - Lang-Hong Wang; Jia-Hong Li; Xu-Rui Li; Yu-Xi Hu; Rui Wang; Xin-An Zeng (Innovative Food Science & Emerging Technologies, 2026)

Chitosan composite packaging film loaded with luteolin-superoxide dismutase nano-micelles: Enhancing food preservation performance - Pei Wu; Yilin Che; Rui Zhou; Yixin Tang; Lei Guo; Baiqiao Chen; Xinran Yan; Shanli Wu; Chang Liu; Mujie Kan; Jizhou Zhang; Xi Yang; et al. (Food Research International, 2026)

Lactiplantibacillus plantarum SP055 pretreatment attenuates experimental colitis in association with partial preservation of epithelial integrity and microbial-metabolic homeostasis - Jianwei Zang; Xiaotong Hao; Yibo Shi; Xia Fan; Yimeng Kou; Xiaogan Zhao; Qiaoya Mo; Di Yu; Jiamin Xu; Chunling Meng; Chang Xu; Luyao Xiao; et al. (Food Bioscience, 2026)

Oxygen-vacancy-rich Na2Ti3O7/Ti3C2Tx arrays via H2O2 etching for humidity sensors - Xinlu Zhao; Hang Yue; Chuanyu Guo; Xin Dong; Tingting Wang; Rui Gao; Xiaoli Cheng; Yingming Xu (Chemical Engineering Journal, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

CRISPR/Cas9 system inhibits largemouth bass virus infection in vitro and in vivo - Rui-Long He; Mao-sheng He; Xin-Yuan Jiang; Yi-Wang; Hao-Liang; Xiang-Yi Bu; Kun Xu; Fei Ling; Gao-Xue Wang; Hai-Feng Jiang (Aquaculture, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Endogenous nitric oxide production induced by pulsed electric field modulates postharvest quality of mango - Ben Yu; Runyu Yao; Dongyang Xu; Tingshi He; Wenhao Xiao; Wenhong Gao; Junhu Cheng; Zhong Han; Xin-An Zeng; Rui Wang (Food Research International, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Carbon-supported nZVI mediates Fe oxides-DOM interactions to regulate Cd and As bioavailability in co-contaminated soils - Jianhua Guo; Yan Wu; Heng Zhang; Rui Wang; Yue Zhao; Xin Fan; Shuaitao Feng; Zuben Xu (Journal of Environmental Chemical Engineering, 2026)

Copper nanoparticles enhance azo dye decolorization by Shewanella putrefaciens CN32: enhanced effect and underlying mechanisms - Bai-Hang Zhao; Rui-Xuan Liu; Bing-Lin Zhang; Xin-Yu Zhang; Xu-Ming Liu (Journal of Environmental Sciences, 2026)

Assessment of oligosaccharide addition on in vitro digestion, hydrolysate absorption, and in vivo digestive enzyme activity of milk/soy proteins - Qiaoya Mo; Tao Lin; Yihan Lin; Chang Xu; Xin Rui; Wei Li (Food Chemistry, 2026)

Secondhand and thirdhand smoke exposure and the risk of liver cancer: a prospective cohort study of 315,833 Chinese never smokers - Zhi Li; Ling-Xiang Xu; Chun-Rui Wang; Zhang-You Guo; Chen-Wei Tang; Xin Dai; Guo-Chao Zhong (Environmental Pollution, 2026)

Developmental light colour influences adult phototaxis and locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Zi-Yu Guo; Xu-Hui Guo; Sheng-Yu Hou; Ke-Jing Feng; Yu-Xin He; Han-Ning Wu; Xin-Hui Chen (Behavioural Processes, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Decoupling pollution sources from health risks of soil metal(loid)s in a mining-impacted agro-ecosystem: Integrating geochemical baselines with bioavailability - Jun Li; Xu-Bin Zhou; Xin-Ying Tuo; Chao Wang; Rui-Qi Yang; Fei Zang (Environmental Geochemistry and Health, 2026)

Exposure to per- and polyfluoroalkyl substances and risk of reproductive system cancers: A systematic review and meta-analysis - Xin Liu; Zhihong Lv; Zixiang Huang; Rui Sun; Dingyu Zhu; Pengcheng Xu; Yiquan Xiong; Xiaowei Guo; Yaxuan Ren; Junhua Zhou (Journal of Environmental Health Science and Engineering, 2026)

A preliminary assessment of ocean wave parameter retrieval and wave energy estimation using spaceborne BDS-R data - Jinwei Bu; Shuhui Liu; Shunshuang Xu; Hui Yang; Tongsu Xiang; Xin He; Yuhang Jiang; Rui Li (Ocean Engineering, 2026)

Microbial distribution and nitrogen transformation under groundwater table fluctuations: Insights from the vadose zone–saturated aquifer - Shida Zheng; Chengzhi Wang; Xin Liu; Donghui Xu; Shufang Wang; Tianfei Chen; Jinsheng Wang; Guanlan Wu; Rui Zuo (Groundwater for Sustainable Development, 2026)

Mechanism and optimization of NaCl removal from soy sauce residue using low pressure superheated steam drying: Role of condensation and moisture migration - Xin Xu; Jian-Bo Liu; Jia-Cheng Guo; Zhi-Hong Xing; Rui-Fang Wang; Qing Xu (Food Chemistry, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Hydrothermal-responsive plasmonic aerogel for dynamic 3D hotspot regulation and ultrasensitive SERS detection of dairy products contaminants - Jing-Xiang Wang; Zhi-Gao Xu; Xin-Rui Wang; Yao-Yao Zhang; Ri-Hui Su; Xin-Xin Zhang; Su-Ming Dai; Wei-Wei Zhu; Xue-Cai Tan; Ke-Jing Huang; Jun Yan (Analytica Chimica Acta, 2026)

Green preparation of graphene oxide-incorporated monoliths for pH-controlled protein enrichment and clinical biomarker detection - Xue Zhang; Fenghua Xu; Rui Wu; Huiying Zhang; Yufei Shi; Zhaosheng Liu; Xin Dong (Analytica Chimica Acta, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

A novel dual-mode sensor based on green-synthesized AuNPs and natural nitrogen-doped CQDs for tobramycin detection: enhanced sensitivity and specificity - Qiang Li; Rui-ling Yin; Xing-yi Yang; Yi-xin Xu; Yan-bing Leng; Xin Liu (Food Research International, 2026)

Improved corrosion resistance of amorphous-containing dual-structured micro-arc oxidation coatings on (Zr0.5Ti0.35Nb0.15)90Al10 high-entropy alloy - Luqi Chai; Xuehui Yan; Yubo Ma; Lijiao Wang; Xin Li; Chungang Guo; Chi Xu; Jiancheng Du; Xiaoyue Jin; Wenbin Xue; Menglu Zhang; Rui Zuo (Chemical Engineering Journal, 2026)

A deep learning multi-branch network method for landslide susceptibility mapping in the Sichuan-Tibet transportation corridor - Jichao Lv; Ruikai Hong; Xin Bao; Renzhe Wu; Xu He; Guoxiang Liu; Rui Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Urbanization exacerbates riverine greenhouse gas (CO2, CH4, N2O) emissions on the Qinghai-Tibet Plateau - Yuwei Huang; Bangguo Wang; Shengying Ye; Queping Yang; Rui Xu; Jian Ma; Qinping Song; Philip K. Hopke; Yuejun He; Xin Zhang; Lijing Wang; Yuanxun Zhang (Journal of Environmental Management, 2026)

Continuous leachate irrigation as an ammonia source enhancing methane oxidation in landfill biocover soils - Ruo He; Rui Zhou; Lei Qian; Likun Xu; Xue Tong; Xin Zhang (Journal of Environmental Management, 2026)

Pulsed electric field facilitated fibrillation of soy protein isolate: preparation, characterization, and functional properties - Dong-Yang Xu; Ben Yu; Wen-Hao Xiao; Zhong Han; Rui Wang; Xin-An Zeng (Food Hydrocolloids, 2026)

Novel approach to binary protein construction via pulsed electric field-induced unfolding: Comprehensive enhancement of chickpea protein properties - Yongxin Teng; Xindong Xu; Boru Chen; Rui Wang; Ting Zhang; Xiangwei Zhu; Yonghui Li; Zhong Han; Xin-An Zeng (Food Hydrocolloids, 2026)

Interfacial environment modulation by nanoneedle-shaped polyaniline for enhanced hydrogen isotope separation by water electrolysis - Rui Li; Guoyu Li; Penghui Xiong; Yuhan Wu; Ruidong Liu; Hang Zhong; Yue Yao; Xin Xiang; Wenhua Luo; Jingsong Xu (Chemical Engineering Journal, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Tracking food-nutrition-carbon footprint evolutions and driving forces of China's megacity: insights from dietary transitions in Chengdu - Xin Xiong; Qin Liu; Pengbo Du; Liwei Yang; Qiuyun Xu; Xinqing Li; Rui Zhao (Journal of Cleaner Production, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Identification of disease-associated gene expression signatures for mechanistic insights and drug prediction in dilated cardiomyopathy-induced heart failure - Wei Yu; Shuai Xu; Xin Tan; Hangyao Zhang; Ruohan Ma; Yiyao Zeng; Anchen Xu; Honghui Tang; Qin Rui; Yahui Song; Yafeng Zhou (Molecular and Cellular Biochemistry, 2026)

Gyrotropic magnetic effect in black phosphorus irradiated with bicircular light - Fangyang Zhan; Xin Jin; Da-Shuai Ma; Jing Fan; Peng Yu; Dong-Hui Xu; Rui Wang (Science Bulletin, 2026)

Closed-loop biorefining of Moringa oleifera branches: unlocking nutraceutical polyphenols and fermentable sugars via NADES-mediated Cascade processing - Rui Zhang; Xin Zhou; Fuyu Yang; Yong Xu (Food Chemistry, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Inhibitory effects of various lignocellulose pretreatment byproducts on xylonic acid biosynthesis by Gluconobacter oxydans - Fan Li; Shuiping Ouyang; Rui Zhang; Xia Hua; Yong Xu; Xin Zhou (Bioresource Technology, 2026)

Xinshuaining preparation ameliorates doxorubicin-induced cardiac injury in heart failure rats by regulating gut microbiota - Qian Nie; Jue Zhao; Sattar Haseeb; Siwei Deng; Xin Zhang; Rui Wang; Xu Luo; Wen Xie (Drug Delivery and Translational Research, 2026)

A novel dual-polarization SAR vegetation index for crop phenology detection - Xin Bao; Rui Zhang; Xu He; Age Shama; Gaofei Yin; Jie Chen; Hongsheng Zhang; Guoxiang Liu; Xianjian Shi (Computers and Electronics in Agriculture, 2025)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Co-inoculation of Bacillus amyloliquefaciens and Pleurotus ostreatus alleviates replanting obstacles in continuously cropped soil by enhancing the soil nutrient cycle and beneficial microorganisms - Xue Luo; Man Xu; Xin-Li Yan; Rui Xing; Yi-Jin Kang; Hong-Wei Wang (Rhizosphere, 2025)

Heterogeneous electro-Fenton like process by iron-doped nickel phosphide catalyst for dibutyl phthalate degradation within a wide pH range - Ruo He; Rui Zhou; Hang Xu; Li-Kun Xu; Chen-Yi Xu; Lian-Feng Mei; Wen-Zhao Zhou; Hong-Yu Meng; Xin Zhang (Journal of Environmental Chemical Engineering, 2025)

Recent advances and perspectives in coordination polymer-based fluorescent sensors for vitamin detection - Zi-Hao Zhao; Zhi-Wei Liu; Xin-Rui Xu; Qian-Yu Yang; Zhao-Yang Tong (Chemical Engineering Journal, 2025)

Integrated multi-omics analysis of UL16-binding protein 2 as a prognostic and immunotherapy biomarker for colorectal cancer - Xin-Yang Qu; Yong Xu; Rui-Min Wu; Gao-Chun Xiao; Ping-Feng Wang; Jin Xie; Xu-Sheng Liu (Functional & Integrative Genomics, 2025)

Enhancing performance of SSVEP-based visual acuity via exploiting subject-specific information - Xiaowei Zheng; Boyu Wen; Xin Yan; Guanghua Xu; Rui Zhang (Cognitive Neurodynamics, 2025)

Differential response patterns of bacterial communities in seawater and sediments to the Chaetomorpha valida bloom in sea cucumber Apostichopus japonicus aquaculture ponds - Hongxia Zhang; Kexin Xu; Ronglian Xing; Linqian Wang; Renyu Liu; Xin Wang; Lihong Chen; Rui Li; Zhen Yu; Xuebin Cao; Cao Cheng; Qun Su (Marine Pollution Bulletin, 2025)

Removal of insoluble barium scales from reverse osmosis membranes by grafting molecular springs - Xin Wen; Yuyan Hai; Rui Ma; Xu Liang; Yawei Duan; Jingyun Chen; Hui Wei; Rihua Xiong (Desalination, 2025)

Interfacial engineering of 0D/3D CeO2/BA nanoarchitectures for highly efficient and selective CO2 photo-reduction to CH4 based on full-spectrum solar-energy utilization - Rui Xu; Chonghai Deng; Chengchen Wang; Yibin Zhu; Yonghui Tong; Zheng Chen; Peipei Sun; LiLi Wang; Lei Yang; Xin Liang; Yiping Wu; Jing Huang; et al. (Chemical Engineering Journal, 2025)

Fusarium infection alters the effects of vegetable residue and its compost on nitrous oxide emissions from acid soil - Yumeng Xu; Xiaoxiao Xiang; Waqar Ahmed; Junhui Yin; Owen Fenton; Wenxuan Shi; Jiaqi Wang; Ruixue Chang; Rui Liu; Hao Chen; Guorong Xin; Qing Chen (Applied Soil Ecology, 2025)

An optimal sequential physical retrieval system for retrieving high-accuracy diurnal atmospheric gases from FY-4B/GIIRS: Theory, algorithm and evaluation - Zhenxing Liang; Dasa Gu; Xin Li; Zijie Xu; Xiangyunong Cao; Heming Bai; Rui Li; Chengxing Zhai; Hui Su; Alexis K.H. Lau (Remote Sensing of Environment, 2025)

Selective separation and stepwise recovery of rare earth and aluminum from magnesium salt-based ionic rare earth leaching liquor - Xin Chen; Sihan Ouyang; Zhouyi Chai; Jianfeng Xu; Rui Kang; Yanfei Xiao; Zhifeng Xu (Journal of Environmental Chemical Engineering, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

The synergistic effects of entomopathogenic fungus Cordyceps javanica and parasitoid Tamarixia radiata in Asian citrus psyllid management - Pei-Ping Xu; Xin-Yi Chen; Jia-Rui Wang; Zi-Tong Lu; Marguerite Mukangango; Wen-Sang; Bao-Li Qiu; Li-He Zhang; Shaukat Ali (Crop Protection, 2025)

Effects of reversing the light-dark cycle on growth performance and intestinal health in heat-stressed broilers - Huiyuan Rui; Xiangyang Xu; Fei Song; Aige Han; Meiwei Lv; Xin Kang; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Elucidating the anti-aging bioactive compounds and mechanisms of Jingfang Granules formula based on network pharmacology and Caenorhabditis elegans - Rui Zhao; Taili Zhao; Tingting Shi; Chuanjiao Feng; Honghua Li; Ying Xu; Qingqing Zhang; Xin Yin; Jingchun Yao; Guimin Zhang; Xuekui Xia (Biogerontology, 2025)

Structurally diverse abietane diterpenoids from the whole plants of Salvia przewalskii Maxim. With anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Tong Zhang; Shuang Xu; Xin Qiao; Guo-Shun Zhang; Qiong Zhang (Phytochemistry, 2025)

Enhancement of chickpea protein functionalities through higher-intensity pulsed electric field: Insights into protein aggregations and structural changes - Yongxin Teng; Yabin Wang; Xindong Xu; Rui Wang; Boru Chen; Langhong Wang; Fuchao Zhan; Zhong Han; Yonghui Li; Xiangwei Zhu; Xin-An Zeng (Food Hydrocolloids, 2025)

Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

Ferroptosis: Disease Associations and Therapeutic Target Exploration - Hailing Wang; Liwei Jia; Rui Yin; Shujun Xu; Xin Meng (Journal of Molecular Neuroscience, 2025)

Identification and bioactivity evaluation of ring-opening and lactone forms of enterolactone from sheep fed flaxseed cake - Cong-Cong Zhuang; Chun-Rui Liu; Hai-Yan Xu; Xin-Yue Yang; Dan-Dan Wu; Zhong Zheng; Li-Wei Wang; Zheng Liu; Chao-Mei Ma (Natural Product Research, 2025)

Intelligently responsive PVDF MF membrane with improved antifouling and easy-cleaning performance for efficient separation of oil-water emulsion - Aida Aibulatova; Lin Yu; Zhen-Liang Xu; Jia-Rui Yang; Rui Jia; Yin-Xin Fang (Journal of Environmental Chemical Engineering, 2025)

Amelioration of Kluyveromyces marxianus GY-8 on high-fat diet-induced obesity and gut microbiota dysbiosis - Nanyu Tang; Xiaogan Zhao; Tao Lin; Yihan Lin; Chang Xu; Kai Ma; Changliang Zhang; Feng Ji; Ghahvechi Chaeipeima Mahsa; Luyao Xiao; Xin Rui; Wei Li (Food Bioscience, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Rational design and pairing of single-domain antibodies for developing rapid detection methods for botulinum neurotoxins A and B - Ruomei Lv; Jiaxin Li; Xinyu Fang; Li Tang; Rui Shi; Jin Wang; Wenjing Zhang; Jinglin Wang; Guangyu Zhao; Jing Wang; Shan Gao; Xuefang Xu; et al. (Analytica Chimica Acta, 2025)

Time-series InSAR landslide three-dimensional deformation prediction method considering meteorological time-delay effects - Jichao Lv; Rui Zhang; Xin Bao; Renzhe Wu; Ruikai Hong; Xu He; Guoxiang Liu (Engineering Geology, 2025)

Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

Diatomic "catalytic/co-catalytic" Fe/Mo catalysts promote Fenton-like reaction to treat organic wastewater through special interfacial reaction enhancement mechanism - Zhen Liu; Xin-Yi Xu; Fei Xu; Rui-Dian Su; Bin Li; Fang Zhang; Xing Xu; Yan Wang; De-Fang Ma; Bao-Yu Gao; Qian Li (Water Research, 2025)

Global rehabilitation research equality index across health conditions during 1990–2019: an alignment analysis between bibliographic and epidemiological data - Xin Guo; Jiakang Huo; Wanwei Dai; Tong Wang; Han Xiao; Wenjing Zhao; Xuanyu Shi; Xueheng Wang; Yang Gao; Zhi Li; Rui Zhan; Wenli Xu; et al. (Science Bulletin, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Unraveling Neurotoxicity Discrepancies: Comparative In vitro and In vivo Analysis of Colistin and Polymyxin B and the Underlying Mechanisms - Rui Yang; Debiao Xiang; Fang Yuan; Yuan Yang; Pengkai Wang; Bing Xu; Xin Li (Molecular Neurobiology, 2025)

Experimental investigation on ammonia‑nitrogen adsorption performance of ZSM-5 molecular sieve prepared from coal gangue and fly ash - Qing-Wei Li; Ye-Rui Zhu; Li-Feng Ren; Wen-Ting Xu; Yu-Xin Miao; Yang Xiao; Cai-Ping Wang (Journal of Water Process Engineering, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Structural evolution of Ni-Ce bimetallic alloy on Al2O3 support in methane dry reforming: Achieving sustainability and high-efficiency reaction through cerium modulation strategy - Xu Ma; Wei-Wei Yang; Jia-Rui Zhang; Xin-Yuan Tang (Fuel, 2025)

Fat substitute in salad dressing: The role of soybean oil body self-aggregates in enhancing texture and rheological property - Xiaoyu Li; Rui Liu; Xin Lv; Ikram Alouk; Shuai Chen; Wenlu Li; Song Miao; Yanbo Wang; Duoxia Xu (Food Research International, 2025)

Highly selective ppb-level Cl2 sensor at room temperature based on ZIF-8 coated MIL-68(In)-derived hexagonal tubes - Sumin Wang; Rui Gao; Ming Zheng; Xianfa Zhang; Xiaoli Cheng; Yingming Xu; Shan Gao; Xin Zhou; Lihua Huo (Chemical Engineering Journal, 2025)

Functional characterization and site-directed mutagenesis of a novel UDP-glycosyltransferase from Panax japonicus var. major - Lu Mou; Yang Zhang; Yu-Xin Zhuang; Rui-Fang Ren; Ran Xu; Ling Yang; Shao-Peng Zhang; Deng-Xiang Du (Planta, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Regulation roles of dre-miR-187 in neurological damage by low concentration toluene in zebrafish - Shu-Hui Men; Jia-Yun Xu; Zhen-Guang Yan; Jin-Zhe Du; Ming-Rui Li; Zi-Ye Wang; Chen Liu; Xin Zheng (Journal of Cleaner Production, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

Transcription combined metabolic analysis reveals the mechanism of potassium phosphate enhances resistance to walnut anthracnose (Colletotrichum gloeosporioides) - Guifang Wang; Yuantao Yao; Haifeng Xu; Kun Xiang; Meiyong Zhang; Junpei Zhang; Rui Zhang; Xin Chen (Postharvest Biology and Technology, 2024)

β-Caryophyllene oxide inhibits lysine acetylation of histones in Fusarium proliferatum to block ribosomal biosynthesis and function - Hong-Xin Liao; Jing Yang; Jin-Rui Wen; Hong-Yan Nie; Jun Zhao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Pesticide Biochemistry and Physiology, 2024)

High-performance COFs composite nanofiltration membrane fabricated by organobase catalyst - Lin Yu; Jia-Yue Dai; Zhen-Liang Xu; Yin-Xin Fang; Rui Jia; Yong-Jian Tang (Desalination, 2024)

Unraveling the chloride ion capture capability of nitrogen-doped porous carbon for capacitive deionization and desalination battery - Huazeng Yang; Rui Zhang; Zhiyuan Liu; Xin Xu; Yishuo Teng; Ming Hou; Guangshuai Zhang; Yongzhao Hou; Guangwu Wen; Dong Wang (Chemical Engineering Journal, 2024)

Hexavalent chromium reduces testosterone levels by impairing lipophagy and disrupting lipid metabolism homeostasis: Based on a metabolomic analysis - Qian Xue; Le Zhang; Rui Wang; Jiayunzhu Xu; Chaofan Wang; Shidi Gao; Xin Fang; Chunyang Meng; Rifeng Lu; Li Guo (Toxicology, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Selective metallization of polymer based on nanoscale tungsten oxide laser activators for advanced electronics - Haoran Xu; Feifan Yu; Jin Feng; Rui Xu; Jiameng Huang; Jia-Xin Wang; Tao Zhou (Chemical Engineering Journal, 2024)

Farrerol Alleviates Cerebral Ischemia–Reperfusion Injury by Promoting Neuronal Survival and Reducing Neuroinflammation - Rui Zhao; Xin Zhou; Zhiyuan Zhao; Wenhao Liu; Mengfei Lv; Zhaolong Zhang; Changxin Wang; Tianli Li; Zixiong Yang; Qi Wan; Rui Xu; Yu Cui (Molecular Neurobiology, 2024)

Exploring the spatial patterns of landslide susceptibility assessment using interpretable Shapley method: Mechanisms of landslide formation in the Sichuan-Tibet region - Jichao Lv; Rui Zhang; Age Shama; Ruikai Hong; Xu He; Renzhe Wu; Xin Bao; Guoxiang Liu (Journal of Environmental Management, 2024)

Stochastic process is main factor to affect plateau river fish community assembly - Xiaoxuan Li; Qigong Xu; Rui Xia; Nan Zhang; Shuping Wang; Sen Ding; Xin Gao; Xiaobo Jia; Guangxia Shang; Xiaofei Chen (Environmental Research, 2024)

Fe2O3@ZrO2 catalyst derived from MOF-on-MOF for direct CO2 hydrogenation to light olefins - Fan Xu; Xin Meng; Rui Zhao; Daoming Jin; Wenhua Dai; Dandan Yang; Zhong Xin (Chemical Engineering Journal, 2024)

In-situ controllable preparation of ZIF-8-wrapped ZnO heterojunction nanorods array for ppb-level Cl2 detection operated at near room temperature - Xiaoqian Meng; Rui Gao; Ming Zheng; Xin Zhou; Xianfa Zhang; Xiaoli Cheng; Yingming Xu; Shan Gao; Lihua Huo (Chemical Engineering Journal, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

SSVEP-based visual acuity threshold estimation: linear extrapolation to noise level baseline with various noise definition criteria - Xiaowei Zheng; Xin Wei; Guanghua Xu; Rui Zhang (Cognitive Neurodynamics, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Insulin interacts with PPARγ agonists to promote bovine adipocyte differentiation - Pan−Pan Guo; Xue−Rui Yao; Yong−Nan Xu; Xin Jin; Qiang Li; Chang−Guo Yan; Nam−Hyung Kim; Xiang−Zi Li (Domestic Animal Endocrinology, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Neoproterozoic back-arc and arc-type magmatisms in the Rutong and Shiquanhe region, west of Tibet: Tectonic implications for the early-stage evolution of the Bangong-Nujiang suture zone and North Lhasa terrane - Xu Zhang; Di-Zhu Cai; Harald Furnes; Wei-Liang Liu; Rui Wang; Wei Li; Xing Liao; Chi Yan; Ru-Xin Ding; Yun Zhong (Precambrian Research, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Fractal characteristics of particle breakage on the coral sands–structure interface during ring shear tests - Houzhen Wei; Li Xin; Hang Ruan; Qi Yao; Xiaolong Ma; Rui Xu (Marine Geophysical Research, 2024)

Ecological impacts of the expansion of offshore wind farms on trophic level species of marine food chain - Lijing Wang; Bangguo Wang; Wenxi Cen; Rui Xu; Yuwei Huang; Xin Zhang; Yinghui Han; Yuanxun Zhang (Journal of Environmental Sciences, 2024)

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Manganese disrupts the maturation and degradation of axonal autophagosome leading to hippocampal synaptic toxicity in mice via the activation of LRRK2 on phosphorylation of Rab10 - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Bin Xu (Science of The Total Environment, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

Recovery hydrotalcite from neutralization sludge of acid mine drainage with high manganese for degradation of norfloxacin with activated peroxymonosulfate - Qingsheng Xu; Zhengbo Yue; Rui Deng; Kang Su; Xin Chuai; Kai Zhang; Jin Wang (Chemical Engineering Journal, 2024)

The Relationships Between Danxia Geoheritages and Regional Tectonics in Southern Sichuan Basin: Implications for the Spatial Distribution of Danxia Landforms in China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yan-Jie Yang; Pengju Li; Liang Qiu; Chao-Bin Xu (Geoheritage, 2024)

The maturity, humus content, and microbial metabolic function of sheep manure compost on the Qinghai-Tibet Plateau can be significantly improved by reducing the moisture content - Rui Cai; Xiaohui Cao; Xin Jiang; Chuncheng Xu (Environmental Science and Pollution Research, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Regulation of oxygen vacancy concentration over ZnCr oxide in bifunctional catalyst for the direct conversion of syngas to light olefins - Daoming Jin; Zhong Xin; Xin Meng; Wenhua Dai; Bowen Xu; Rui Zhao; Fan Xu; Dandan Yang (Chemical Engineering Journal, 2024)

Inverse kinetic isotope effect of proton and deuteron permeation through pyridinic N-doped graphene - Jingwen Ba; Jinfan Chen; Renjin Xiong; Jingsong Xu; Haibo Li; Xiayan Yan; Cheng Qin; Rui Li; Qifa Pan; Xinxin Tan; Tao Tang; Xin Xiang; et al. (Chemical Engineering Journal, 2024)

Application of alkaline sludge based LDHs in Cd and Cu polluted wastewater remediation: Process and mechanism - Qingsheng Xu; Zhengbo Yue; Rui Deng; Xinquan Wang; Xiao He; Xin Chuai; Shaoping Wang; Jin Wang (Journal of Water Process Engineering, 2023)

Conversion of highly polymerized lignin into monophenolic products via pyrolysis: A comparative study of acidic and alkaline depolymerization pretreatments using deep eutectic solvents - Xin Yue; Jinxin Lin; Terhi Suopajärvi; Otto Mankinen; Atte Mikkelson; Rui Liu; Harri Huttunen; Liheng Chen; Chunlin Xu; Ville-Veikko Telkki; Shirong Sun; Henrikki Liimatainen (Chemical Engineering Journal, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

A2DWQPE: Adaptive and automated data-driven water quality parameter estimation - Yiyun Hu; Fangling Pu; Chuishun Kong; Rui Yang; Hongjia Chen; Xin Xu (Journal of Hydrology, 2023)

Highly dispersed Fe/EG catalysts assisted by ammonium citrate and their application in CO2 hydrogenation to olefins - Rui Zhao; Xin Meng; Wenhua Dai; Daoming Jin; Bowen Xu; Fan Xu; Dandan Yang; Zhong Xin (Fuel, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Process and mechanism of recovering layered double hydroxides (LDHs) from acid mine drainage (AMD) and synergetic removal of manganese - Qingsheng Xu; Zhengbo Yue; Rui Deng; Xinquan Wang; Xin Chuai; Kai Zhang; Jin Wang (Journal of Environmental Chemical Engineering, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Lactiplantibacillus plantarum Regulated Intestinal Microbial Community and Cytokines to Inhibit Salmonella typhimurium Infection - Rui-Han Liu; An-Qi Sun; Ye Liao; Zheng-Xu Tang; Shi-Han Zhang; Xin Shan; Jing-Tao Hu (Probiotics and Antimicrobial Proteins, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Controlled release of Lactiplantibacillus plantarum by colon-targeted adhesive pectin microspheres: Effects of pectin methyl esterification degrees - Danling Xu; Xiaogan Zhao; Ghahvechi Chaeipeima Mahsa; Kai Ma; Changliang Zhang; Xin Rui; Mingsheng Dong; Wei Li (Carbohydrate Polymers, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

FHB resistance conferred by Fhb1 is under inhibitory regulation of two genetic loci in wheat (Triticum aestivum L.) - Guoqiang Li; Yang Yuan; Jiyang Zhou; Rui Cheng; Ruitong Chen; Xianmin Luo; Jinxing Shi; Heyu Wang; Boyang Xu; Youyu Duan; Jinkun Zhong; Xin Wang; et al. (Theoretical and Applied Genetics, 2023)

Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry - Xu Pang; Jing Qiu; Zhaoyang Zhang; Pi Li; Jiangtao Xing; Xin Su; Guiqiao Liu; Changyuan Yu; Rui Weng (Food Chemistry, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

A systematic knowledge pedigree analysis on green governance - Rui Yang; Yingwen Chen; Jie Zhong; Yujin Xu; Xin An (Environment, Development and Sustainability, 2023)

Crushing combined with high–frequency turning can promote material degradation of sheep manure compost on the Qinghai–Tibet Plateau by improving the microbial metabolic function - Rui Cai; Xinyu Cui; Xiaohui Cao; Xin Jiang; Rongze Wang; Chuncheng Xu (Journal of Environmental Chemical Engineering, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

The circadian regulation of extracellular ATP - Xin Wang; Yu-Ting Dong; Xiu-Ming Hu; Ji-Zhou Zhang; Nan-Rui Shi; Yan-Qin Zuo; Xu Wang (Purinergic Signalling, 2023)
Extracellular ATP is a potent signaling molecule released from various cells throughout the body and is intimately involved in the pathophysiological functions of the nervous system and immune system by activating P2 purinergic receptors. Recent increasingly studies showed that extracellular ATP exhibits circadian oscillation with an approximately 24-h periodicity, which participates in regulatory pathways of central oscillator suprachiasmatic nucleus and peripheral oscillator bladder, respectively. Oscillators modulate the protein expression of ATP release channels and ectonucleotidase activity through clock genes; indeed, real-time alterations of ATP release and degradation determine outcomes of temporal character on extracellular ATP rhythm. The regulatory pathways on extracellular ATP rhythm are different in central and peripheral systems. In this review, we summarize the circadian rhythm of extracellular ATP and discuss several circadian regulatory pathways in different organs via ATP release and degradation, to provide a new understanding for purinergic signaling in the regulatory mechanism of circadian rhythm and a potential target to research the circadian regulation of extracellular ATP in other circadian oscillators.

Manganese-induced α-synuclein overexpression promotes the accumulation of dysfunctional synaptic vesicles and hippocampal synaptotoxicity by suppressing Rab26-dependent autophagy in presynaptic neurons - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Yu Deng; Xin Li; Bin Xu (Science of The Total Environment, 2023)

Friction induced mechanochemistry: self-adaptive lubrication through in-situ tribo-click system - Rui Dong; Yunlei Zhang; Hao-Zhe Xu; Luyao Bao; Shuanhong Ma; Xin-Gang Wang; Qiangliang Yu; Meirong Cai; Feng Zhou; Weimin Liu (Chemical Engineering Journal, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Bioaccessibility and bioavailability evaluation of heavy metal(loid)s in ginger in vitro: Relevance to human health risk assessment - Xin Xu; Jinhang Wang; Huihui Wu; Rui Lu; Jun Cui (Science of The Total Environment, 2023)

Selective detection of trace carbon monoxide at room temperature based on CuO nanosheets exposed to (111) crystal facets - Yuanyuan Wu; Ji Li; Mingsong Lv; Xianfa Zhang; Rui Gao; Chuanyu Guo; Xiaoli Cheng; Xin Zhou; Yingming Xu; Shan Gao; Zoltán Major; Lihua Huo (Journal of Hazardous Materials, 2023)

Habitat quality dynamics in China's first group of national parks in recent four decades: Evidence from land use and land cover changes - Xin Chen; Le Yu; Yue Cao; Yidi Xu; Zhicong Zhao; Youbo Zhuang; Xuehua Liu; Zhenrong Du; Tao Liu; Bo Yang; Lu He; Hui Wu; et al. (Journal of Environmental Management, 2023)

Combination of pulsed electric field and pH shifting improves the solubility, emulsifying, foaming of commercial soy protein isolate - Rui Wang; Lang-Hong Wang; Qing-Hui Wen; Fei He; Fei-Yue Xu; Bo-Ru Chen; Xin-An Zeng (Food Hydrocolloids, 2023)

Boosting elementary steps kinetics towards energetic alkaline hydrogen evolution via dual sites on phase-separated Ni–Cu–Mn/hydroxide - Zhimin Li; Sisi Xin; Yirong Zhang; Zhengfu Zhang; Chengping Li; Caiju Li; Rui Bao; Jianhong Yi; Mingli Xu; Jinsong Wang (Chemical Engineering Journal, 2023)

Clinical Decision on Disorders of Consciousness After Acquired Brain Injury: Stepping Forward - Rui-Zhe Zheng; Zeng-Xin Qi; Zhe Wang; Ze-Yu Xu; Xue-Hai Wu; Ying Mao (Neuroscience Bulletin, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

Identification of Ferroptotic Genes in Spinal Cord Injury at Different Time Points: Bioinformatics and Experimental Validation - Yu Kang; Qiangwei Li; Rui Zhu; Shuang Li; Xin Xu; Xuanming Shi; Zongsheng Yin (Molecular Neurobiology, 2022)

Experimental study on the mechanical properties and energy evolution of hard rock during water immersion - Fan-Bo Wei; Bing-Rui Chen; Rui Wang; Guo-Liang Li; Tao Li; Xu Wang; Xin-Hao Zhu (Arabian Journal of Geosciences, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Mutual impacts and interactions of antibiotic resistance genes, microcystin synthetase genes, graphene oxide, and Microcystis aeruginosa in synthetic wastewater - Shichao Wu; Xiyan Ji; Xin Li; Jing Ye; Wenwu Xu; Rui Wang; Meifang Hou (Environmental Science and Pollution Research, 2022)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Mechanism of environmental factors regulating water consumption of Larix gmelinii forests - Xin Zhang; Qiuliang Zhang; Zhihong Xu; Rui Wang; Yanan Jian; Jingfu Yang; Changlei Sun; Jiafu Wang (Journal of Soils and Sediments, 2021)

Clarification of the etiology of peach bacteria leaf shot hole caused by Pantoea spp. in Henan Province, China, based on morphological characteristics and multi-locus sequences analysis - Rui Zang; Lu-lu Song; Chao Xu; Xin-ming Yin; Zhan-xiang Qiao; Yue-hua Geng; Meng Zhang (European Journal of Plant Pathology, 2021)

Microseismic source location method based on a velocity model database and statistical analysis - Bing-Rui Chen; Tao Li; Xin-Hao Zhu; Fan-Bo Wei; Xu Wang; Ming-Xing Xie (Arabian Journal of Geosciences, 2021)

The mTOR/NF-κB Pathway Mediates Neuroinflammation and Synaptic Plasticity in Diabetic Encephalopathy - Ting Xu; Jiao Liu; Xin-rui Li; Yinghua Yu; Xuan Luo; Xian Zheng; Yuan Cheng; Pei-quan Yu; Yi Liu (Molecular Neurobiology, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Cytokinin (6-benzylaminopurine) elevates lignification and the expression of genes involved in lignin biosynthesis of carrot - Ahmed Khadr; Ya-Hui Wang; Rong-Rong Zhang; Xin-Rui Wang; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Genetic variants in Ras/Raf/MEK/ERK pathway are associated with gastric cancer risk in Chinese Han population - Xiaowei Wang; Xu Wu; Junyi Xin; Shuwei Li; Rui Zheng; Dan Guan; Weida Gong; Qinghong Zhao; Meilin Wang; Haiyan Chu; Mulong Du; Guoquan Tao; et al. (Archives of Toxicology, 2020)

In vitro and in vivo evaluation of the antifungal activity of fluoxetine combined with antifungals against Candida albicans biofilms and oral candidiasis - Liuliu Jiang; Linxia Zheng; K airui Sun; Peng Zhou; Rui Xu; Jingyi Gu; Xin Wei (Biofouling, 2020)

PDB-1 from Potentilla discolor Bunge suppresses lung cancer cell migration and invasion via FAK/Src and MAPK signaling pathways - Na-na Meng; Rui-rui Zhang; Chao Liu; Qing Wang; Xin-kun Wang; Xu Guo; Ping-ping Wang; Jin-yue Sun (Medicinal Chemistry Research, 2020)

Risk factors and clinical characteristics of tacrolimus-induced acute nephrotoxicity in children with nephrotic syndrome: a retrospective case-control study - Ping Gao; Xin-Lei Guan; Rui Huang; Xiao-Fang Shang-guan; Jiang-Wei Luan; Mao-Chang Liu; Hua Xu; Xiao-Wen Wang (European Journal of Clinical Pharmacology, 2020)

Genetic variants in circTUBB interacting with smoking can enhance colorectal cancer risk - Ke Zhang; Shuwei Li; Dongying Gu; Kaili Xu; Rui Zheng; Junyi Xin; Yixuan Meng; Shuai Ben; Haiyan Chu; Zhengdong Zhang; Yongqian Shu; Mulong Du; et al. (Archives of Toxicology, 2020)

Chromosome level comparative analysis of Brassica genomes - Wenliang Wang; Rui Guan; Xing Liu; Haorui Zhang; Bo Song; Qiwu Xu; Guangyi Fan; Wenbin Chen; Xiaoming Wu; Xin Liu; Jianbo Wang (Plant Molecular Biology, 2019)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Screening HCV genotype-specific epitope peptides based on conserved sequence analysis and B cell epitope prediction in HCV E2 region - Rui Hua; Xiaoyu Jiang; Lingxia Qi; Shanshan Guan; Ziyu Kuai; Yongbo Qiao; Yan Xu; Xin Gong; Yuhua Shi; Wei Kong; Junqi Niu; Hao Zhang; et al. (Immunologic Research, 2018)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Comparisons of Evaluation Factors and Application Effects of the New [BQ]GSI System with International Rock Mass Classification Systems - Shen Yan-jun; Yan Rui-xin; Yang Geng-she; Xu Guang-li; Wang Shan-yong (Geotechnical and Geological Engineering, 2017)

Inhibition of P2X7 Receptor Ameliorates Nuclear Factor-Kappa B Mediated Neuroinflammation Induced by Status Epilepticus in Rat Hippocampus - Cheng Huang; Xiao-sa Chi; Rui Li; Xin Hu; Hai-xia Xu; Jin-mei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Plasma miR-221/222 Family as Novel Descriptive and Prognostic Biomarkers for Glioma - Rui Zhang; Bo Pang; Tao Xin; Hua Guo; Yi Xing; Shangchen Xu; Bin Feng; Bin Liu; Qi Pang (Molecular Neurobiology, 2016)

Estimation of Permeability from NMR Logs Based on Formation Classification Method in Tight Gas Sands - Deng-Feng Wei; Xiao-Peng Liu; Xiao-Xin Hu; Rui Xu; Ling-Ling Zhu (Acta Geophysica, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

A new bibenzyl derivative with nuclear factor-kappaB inhibitory activity from Schefflera arboricola (Araliaceae) - Hang Li; Zi-Zhe Cai; Long-Ping Zhu; Xin-Jun Xu; Shao-Rui Chen; De-Po Yang; Zhi-Min Zhao (Natural Product Research, 2015)

Effect of grazing on the abundance of functional genes associated with N cycling in three types of grassland in Inner Mongolia - K. Ding; L. Zhong; X. P. Xin; Z. H. Xu; X. M. Kang; W. J. Liu; Y. C. Rui; L. L. Jiang; L. Tang; Y. F. Wang (Journal of Soils and Sediments, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Gabapentin Enhances the Morphine Anti-Nociceptive Effect in Neuropathic Pain via the Interleukin-10-Heme Oxygenase-1 Signalling Pathway in Rats - Yu-Hua Bao; Quan-Hong Zhou; Rui Chen; Hao Xu; Lu-Lu Zeng; Xin Zhang; Wei Jiang; Dong-Ping Du (Journal of Molecular Neuroscience, 2014)

Consumption of hydrogen-rich water alleviates renal injury in spontaneous hypertensive rats - Hai-Guang Xin; Bei-Bei Zhang; Zhi-Qin Wu; Xiao-Feng Hang; Wen-Sheng Xu; Wu Ni; Rui-Qi Zhang; Xiao-Hui Miao (Molecular and Cellular Biochemistry, 2014)

Expression and Functional Significance of Ezrin in Human Brain Astrocytoma - Jie Mao; Xian-rui Yuan; Shan-shui Xu; Xiao-chun Jiang; Xin-tong Zhao (Cell Biochemistry and Biophysics, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Antidepressant-like effect of flaxseed secoisolariciresinol diglycoside in ovariectomized mice subjected to unpredictable chronic stress - Xing Ma; Rui Wang; Xin Zhao; Chong Zhang; Jiao Sun; Jianxin Li; Lu Zhang; Tuo Shao; Lina Ruan; Liang Chen; Ying Xu; Jianchun Pan (Metabolic Brain Disease, 2013)

Exogenous hydrogen sulfide attenuates diabetic myocardial injury through cardiac mitochondrial protection - Xin Zhong; Leihong Wang; Yuwen Wang; Shiyun Dong; Xiaoning Leng; Jing Jia; Yajun Zhao; Hulun Li; Xinying Zhang; Changqing Xu; Guangdong Yang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2012)

Synthesis and studies on antidepressant activity of 2′,4′,6′-trihydroxychalcone derivatives - Xin Sui; Ying-Chun Quan; Yue Chang; Rui-Peng Zhang; Yin-Feng Xu; Li-Ping Guan (Medicinal Chemistry Research, 2012)

Risk of high-grade bleeding in patients with cancer treated with bevacizumab: a meta-analysis of randomized controlled trials - Xiao Feng Hang; Wen Sheng Xu; Jun Xue Wang; Lei Wang; Hai Guang Xin; Rui Qi Zhang; Wu Ni (European Journal of Clinical Pharmacology, 2011)

Estimate of eddy energy generation/dissipation rate in the world ocean from altimetry data - Chi Xu; Xiao-Dong Shang; Rui Xin Huang (Ocean Dynamics, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Isolation and simultaneous determination of two benzofurans in Radix Eupatorii Chinensis - Xiao-Ling Xie; Xin-Jun Xu; Rui-Ming Li; Jin-Zhi Wan; Chun-Yan Xie; De-Po Yang; Xiao Chen (Natural Product Research, 2010)

Testicular toxicity induced by dietary cadmium in cocks and ameliorative effect by selenium - Jin-Long Li; Rui Gao; Shu Li; Jin-Tao Wang; Zhao-Xin Tang; Shi-Wen Xu (BioMetals, 2010)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)